Evaluation of effect of body mass index and weight loss on survival of patients with nasopharyngeal carcinoma treated with intensity-modulated radiation therapy - Lin, Yu-Hsuan (Radiat Oncol, 2015)
BACKGROUND: Previous studies report body-mass index (BMI) and percent weight loss (WL) to have prognostic significance when treating patients with nasopharyngeal carcinoma (NPC). However, most of these investigations studied patients treated using different radiotherapeutic techniques. We evaluated the predictive effect of these two nutrition-related measurements on therapeutic outcome in NPC patients who only received intensity-modulated radiation therapy (IMRT) as part of their total treatment program. METHODS: We retrospectively studied NPC patients treated with IMRT from January 2006 to February 2012. Cox proportional hazards was used to test the association of pretreatment BMI (<23 kg/m(2) vs. ≥23 kg/m(2)) and percent weight loss (≥5 % vs. <5 %) during therapy and related survival rates while controlling for various potential confounders. RESULTS: Eighty-one (34 %) of the 238 patients had BMIs ≥23 kg/m(2) at pretreatment and 150 (63 %) had significant (≥5 %) weight loss. Median follow-up time was 41.71 months; median radiotherapy was 7.46 ± 0.77 weeks. Those with BMIs ≥23 kg/m(2) did not have a better 3-year overall survival (p = 0.672), 3-year disease specific survival (p = 0.341), 3-year locoregional free survival (p = 0.281), or 3-year distant metastatic free survival (p = 0.134). Those with significant WL (≥5 %) did not have worse 3-year clinical endpoints, even after stratifying magnitude of weight loss by BMI category. In sensitivity test, the adjusted hazard ratio remained statistically insignificant using different cutoffs for BMIs and percent weight loss. CONCLUSIONS: This study found no significant relationship between BMI and percent weight loss on survival of NPC patients receiving IMRT based therapy. Further studies might want to consider other nutrition related factors as prognostic indicators when studying the correlate between malnutrition and survival in this population. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13014-015-0443-3) contains supplementary material, which is available to authorized users.